Modified glass powder, method for preparing the same, photovoltaic silver paste and solar cell
Patent Information
- Application Number
- CN202610830622.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-10
- Publication Date
- 2026-10-13
- Estimated Expiration
- 2046-06-10
AI Technical Summary
虽然玻璃粉在光伏银浆中的占比较小,但是由于玻璃粉的粒径小,比表面积大,范德华力强,表面原子比例高,处于高能量状态,故玻璃粉极易吸附水、CO2并发生团聚
[0014]本发明提供的改性玻璃粉的制备方法,通过化学接枝的方法将官能化高分子链接枝在玻璃粉表面,官能化高分子链与玻璃粉表面的Si-OH基团发生脱水缩合,形成Si-O-Si共价键,这种化学键在经过搅拌、三辊、印刷后依然牢牢存在,为玻璃粉提供终生有效的分散性。经过官能化高分子链接枝后,玻璃粉的表面由亲水性变成亲油性,与光伏银浆中的载体具有更好的相容性,改善光伏银浆的印刷性能;同时,高分子改性的玻璃粉减弱了玻璃的团聚,分散性和储存性更佳,并有利于改善经光伏银浆制备得到的电极的电性能。
Smart Images

Figure CN122356843B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of solar cell technology, and in particular to a modified glass powder and its preparation method, photovoltaic silver paste, and solar cells. Background Technology
[0002] Photovoltaic silver paste is a core material for preparing metal electrodes for solar cells, mainly consisting of three components: silver powder, carrier, and glass powder. Although glass powder accounts for a small proportion of photovoltaic silver paste, its small particle size, large specific surface area, strong van der Waals forces, high surface atomic ratio, and high energy state make it highly susceptible to adsorbing water and CO2 and agglomerating. Agglomerated glass powder severely affects its dispersibility in photovoltaic silver paste, which is a key factor determining the paste's uniformity, stability, and final cell efficiency. Poor dispersibility affects the printing and storage performance of photovoltaic silver paste, ultimately impacting the electrical performance of the electrode. Summary of the Invention
[0003] The purpose of this invention is to provide a method for preparing modified glass powder. The modified glass powder prepared by this method has better compatibility with the carrier in photovoltaic silver paste, and can reduce the agglomeration of glass powder, resulting in better dispersibility and storage properties.
[0004] This invention provides a method for preparing modified glass powder, comprising the following steps: S1: A first solvent, a polymerizing monomer, a structure control agent, and an initiator are mixed and reacted to obtain a polymer chain; then silicon tetrachloride is added to the reaction solution to end-cap the polymer chain, resulting in a first solution containing a functionalized polymer chain; wherein the polymerizing monomer includes one or more of styrene monomers, conjugated diene monomers, and vinyl monomers. S2: Mix the second solvent, the glass powder containing silicon oxide, and the first solution to link the functionalized polymer to the surface of the glass powder, thereby obtaining modified glass powder.
[0005] In one feasible embodiment, the styrene monomer includes one or more of styrene, α-methylstyrene, and p-methylstyrene; the conjugated diene monomer includes one or more of 1,3-butadiene and isoprene; and the vinyl monomer includes one or more of acrylate, acrylonitrile, and methyl vinyl ketone.
[0006] In one feasible embodiment, the structure control agent comprises one or more of ether structure control agents, amine structure control agents, and alkali metal salts; the ether structure control agent comprises one or more of tetrahydrofuran, diethylene glycol dibutyl ether, and crown ethers; the amine structure control agent comprises one or more of N,N-dimethyltetrahydrofurfurylamine, N,N,N,N-tetramethyltetrahydrofurfurylamine, triethylamine, and tetrahydropyrrole; and the alkali metal salt comprises potassium tert-butoxy.
[0007] In one feasible manner, the initiator comprises one or more of alkyllithium, alkali metal, nucleophile, and alkylaluminum-alkali metal complex; the alkyllithium comprises one or more of n-butyllithium, sec-butyllithium, tert-butyllithium, and multifunctional lithium; the alkali metal comprises one or more of lithium, sodium, and potassium; and the nucleophile comprises one or more of sodium hydroxide, sodium alkoxide, and amine nucleophiles.
[0008] In one feasible manner, the first solvent comprises one or more of n-hexane, cyclohexane, benzene, toluene, tetrahydrofuran, diethyl ether, 1,4-dioxane, and diethylene glycol dibutyl ether; and / or, the second solvent comprises one or more of n-hexane, cyclohexane, benzene, toluene, tetrahydrofuran, diethyl ether, 1,4-dioxane, and diethylene glycol dibutyl ether.
[0009] In one possible implementation, the glass powder is silicon oxide; or, the glass powder comprises silicon oxide and one or more of boron oxide, bismuth oxide, zinc oxide, lithium oxide, calcium oxide, tungsten oxide, copper oxide, iron oxide, and tellurium oxide.
[0010] In one feasible implementation, in step S2 above, the mass ratio of the first solution to the glass powder is (0.5~50):100; and / or, the grafting density of the modified glass powder is (0.01~10)×10⁻⁶. -3 nm -2 .
[0011] The present invention also provides a modified glass powder, which is prepared by the modified glass powder preparation method described above.
[0012] The present invention also provides a photovoltaic silver paste, which, by mass percentage, comprises: 85%-92% silver powder, 1%-4% modified glass powder, 0.1%-1% dispersant, 0.4%-1% silicone oil, 0.1%-2% thixotropic agent, 1%-4% organic resin, and 4%-10% organic solvent; wherein the modified glass powder is the modified glass powder as described above or prepared by the modified glass powder preparation method described above.
[0013] The present invention also provides a solar cell including an electrode, said electrode being obtained by sintering a photovoltaic silver paste as described above.
[0014] The modified glass powder preparation method provided by this invention involves chemically grafting functionalized polymers onto the surface of the glass powder. The functionalized polymer chains undergo dehydration condensation with the Si-OH groups on the glass powder surface, forming Si-O-Si covalent bonds. These chemical bonds remain firmly established even after stirring, three-roll milling, and printing, providing lifelong effective dispersibility for the glass powder. After functionalized polymer grafting, the surface of the glass powder changes from hydrophilic to oleophilic, resulting in better compatibility with the carrier in photovoltaic silver paste and improved printing performance. Simultaneously, the polymer-modified glass powder reduces glass agglomeration, improves dispersibility and storage properties, and is beneficial for improving the electrical performance of electrodes prepared from photovoltaic silver paste. Attached Figure Description
[0015] Figure 1 The image shows the sedimentation characteristics of the glass powder used in Comparative Example 1 in an organic solvent.
[0016] Figure 2 The image shows the sedimentation characteristics of the glass powder used in Comparative Example 2 in an organic solvent.
[0017] Figure 3 This is a photograph showing the sedimentation characteristics of the glass powder used in Example 2 in an organic solvent.
[0018] Figure 4 The image shows the SEM image of the glass powder used in Comparative Example 1.
[0019] Figure 5 This is a SEM image of the glass powder used in Comparative Example 2.
[0020] Figure 6 This is an SEM image of the glass powder used in Example 2.
[0021] Figure 7 This is a schematic diagram showing the printing performance (fractured grid) of Comparative Example 1.
[0022] Figure 8 This is a schematic diagram showing the printing performance (fractured grid) of Comparative Example 2.
[0023] Figure 9 This is a schematic diagram of the printing performance (fractured grid) of Example 1.
[0024] Figure 10 This is a schematic diagram showing the printing performance (fractured grid) of Example 2.
[0025] Figure 11 This is a schematic diagram showing the printing performance (fractured grid) of Example 3. Detailed Implementation
[0026] The specific embodiments of the present invention will be described in further detail below. The following examples are used to illustrate the present invention, but are not intended to limit the scope of the present invention. The terms "first," "second," "third," "fourth," etc. (if present) in the specification and claims of the present invention are used to distinguish similar objects and are not necessarily used to describe a specific order or sequence.
[0027] Photovoltaic silver paste is a core material for preparing metal electrodes in solar cells, mainly consisting of three components: silver powder, carrier, and glass powder. Although glass powder accounts for a small proportion of photovoltaic silver paste, its small particle size, large specific surface area, strong van der Waals forces, high surface atomic ratio, and high energy state make it highly susceptible to adsorbing water and CO2 and agglomerating. Agglomerated glass powder severely affects its dispersibility in photovoltaic silver paste, which is a key factor determining the uniformity, stability, and final cell efficiency of the paste. Poor dispersibility is the root cause of many quality problems. First, during the printing stage, glass agglomeration leads to unstable rheological properties of the paste, easily clogging the screen and causing problems such as "bamboo-like" lines, broken grids, and edge burrs. Second, during the sintering stage, localized aggregation of the glass phase leads to over-etching of the silicon wafer in that area (damaging the PN junction), while areas lacking glass lack sufficient etching and cannot form good conductive channels; therefore, glass agglomeration causes leakage current, low parallel resistance, and efficiency loss in the solar cell. Secondly, glass agglomeration leads to uneven conductive channels, increasing and destabilizing the series resistance (Rs). Finally, the tendency of glass powder to agglomerate makes the storage of photovoltaic silver paste extremely difficult, requiring a strictly sealed environment.
[0028] In the chemical modification of glass powder, a common method is the chemical grafting method using silane coupling agents. After partial hydrolysis of -Si(OR')3, it undergoes dehydration condensation with the Si-OH on the glass powder surface, forming Si-O-Si covalent bonds. These silane coupling agents are mostly short-chain compounds with molecular weights of only a few hundred, such as Si-69, Si-747, APS, and KH-570 / 590. The modified glass powder has limited dispersion in silver paste. Another approach involves mixing glass powder with a solution containing a polymer (such as polyvinylpyrrolidone, PVP, or polyacrylic acid, PAA), then removing the solvent, allowing the polymer to coat the glass powder. However, this polymer is only physically adsorbed onto the glass powder and does not form chemical bonds. During subsequent silver paste preparation involving prolonged stirring, multiple three-roll printing processes, or long-term shear printing, this physically adsorbed polymer quickly peels off the glass powder, resulting in poor dispersibility, long-term printing stability, and good storage properties.
[0029] To solve, or at least partially solve, the above-mentioned technical problems, embodiments of the present invention provide a method for preparing modified glass powder for photovoltaic silver paste, the method comprising the following steps: S1: A first solvent, a polymerizing monomer, a structure control agent, and an initiator are mixed to allow the polymerizing monomer to undergo a polymerization reaction, resulting in a polymer chain; then, silicon tetrachloride is added to the reaction solution (i.e., a mixed solution of the first solvent, the polymerizing monomer, the structure control agent, and the initiator) to end-cap the polymer chain, resulting in a first solution containing functionalized polymer chains; wherein, the polymerizing monomer includes one or more of styrene monomers, conjugated diene monomers, and vinyl monomers; S2: Mix the second solvent, glass powder containing silicon oxide (e.g., silicon dioxide), and the first solution to link the functionalized polymer to the surface of the glass powder, thereby obtaining modified glass powder.
[0030] In step S1 above, silicon tetrachloride reacts with the polymer chain to obtain a functionalized polymer chain X-SiCl3 (X represents a polymer chain formed by the polymerization of monomers) that can react with glass powder. The -SiCl3 group in the functionalized polymer chain provides a group for reaction with glass powder. In step S2 above, since the glass powder contains silicon oxide, it provides a site (Si-OH group) for reaction with the functionalized polymer chain. The Si-Cl bond at the end of the functionalized polymer chain X-SiCl3 first undergoes a hydrolysis reaction with the bound water on the surface of the glass powder, removing HCl molecules and generating X-Si-(OH). X Then, it undergoes dehydration condensation with the Si-OH on the surface of the glass powder, forming Si-O-Si covalent bonds, thereby grafting the polymer chain X onto the surface of the glass powder to obtain modified glass powder. Since polymer chain X is obtained by polymerization of styrene monomers, conjugated diene monomers, or vinyl monomers, the surface of the glass powder changes from hydrophilic to oleophilic. Furthermore, the larger molecular weight of polymer chain X improves the compatibility of the glass powder with the carrier in photovoltaic silver paste, effectively improving the printing performance of the photovoltaic silver paste. Simultaneously, the polymer-modified glass powder reduces glass agglomeration, resulting in better dispersibility and storage properties, and is beneficial for improving the electrical performance of electrodes prepared from photovoltaic silver paste. Moreover, because the polymer chain forms Si-O-Si covalent bonds on the surface of the glass powder through grafting, these chemical bonds remain firmly established after stirring, three-roll milling, and printing, providing lifelong effective dispersibility for the glass powder.
[0031] In particular, the entire S1 step is carried out under an anhydrous, oil-free, nitrogen atmosphere. Meanwhile, each raw material in the S1 step (including the first solvent, polymerization monomer, structure control agent, initiator, and silicon tetrachloride) is purified by vacuum distillation to ensure the purity of the raw materials.
[0032] In one embodiment, in step S1 above, the styrene monomer includes one or more of styrene, α-methylstyrene, and p-methylstyrene; the conjugated diene monomer includes one or more of 1,3-butadiene and isoprene; and the vinyl monomer includes one or more of acrylate, acrylonitrile, and methyl vinyl ketone.
[0033] In one embodiment, the polymerization monomers include two monomers: styrene (St) and 1,3-butadiene (BR), and the functionalized polymer chain obtained by polymerization is SBR-SiCl3.
[0034] In one embodiment, in step S1 above, the structure control agent includes one or more of ether structure control agents, amine structure control agents, and alkali metal salts; the ether structure control agent includes one or more of tetrahydrofuran, diethylene glycol dibutyl ether, and crown ethers; the amine structure control agent includes one or more of N,N-dimethyltetrahydrofurfurylamine, N,N,N,N-tetramethyltetrahydrofurfurylamine, triethylamine, and tetrahydropyrrole; and the alkali metal salt includes potassium tert-butoxy.
[0035] In one embodiment, in step S1 above, the initiator includes one or more of alkyllithium, alkali metal, nucleophile, and alkylaluminum-alkali metal complex; the alkyllithium includes one or more of n-butyllithium, sec-butyllithium, tert-butyllithium, and multifunctional lithium; the alkali metal includes one or more of lithium, sodium, and potassium; and the nucleophile includes one or more of sodium hydroxide, sodium alkoxide, and amine nucleophiles.
[0036] In one embodiment, in step S1 above, the first solvent includes one or more of n-hexane, cyclohexane, benzene, toluene, tetrahydrofuran, diethyl ether, 1,4-dioxane, and diethylene glycol dibutyl ether.
[0037] In one implementation method, the molecular weight of the polymer chain in step S1 above can be from 0.1 million to 200,000, specifically 0.1 million, 0.5 million, 1 million, 2 million, 5 million, 150,000, 200,000, etc., or any combination of the above values. The molecular weight of the polymer chain is mainly controlled and adjusted by the amount of initiator added.
[0038] In one implementation, in step S1 above, depending on the type of monomer in the reaction system, the mass percentage of the monomer in the reaction solution can be 0.01% to 90%, or 5% to 20%, specifically 0.01%, 1%, 5%, 10%, 15%, 20%, 30%, 40%, 50%, 60%, 70%, 80%, 90%, etc., or any combination of the above values. Depending on the type of monomer in the reaction system, the reaction temperature in step S1 can be -78℃ to 90℃.
[0039] In one embodiment, in step S1 above, the molar ratio of the initiator to the functionalized polymer chain is 1:1, and the molar ratio of the structure control agent to the functionalized polymer chain is 1:1.
[0040] In one embodiment, in step S2 above, the second solvent includes one or more of n-hexane, cyclohexane, benzene, toluene, tetrahydrofuran, diethyl ether, 1,4-dioxane, and diethylene glycol dibutyl ether.
[0041] In one embodiment, in step S2 above, the glass powder is silicon oxide (specifically, it can be silicon dioxide); or, the glass powder includes silicon oxide and one or more of boron oxide, bismuth oxide, zinc oxide, lithium oxide, calcium oxide, tungsten oxide, copper oxide, iron oxide, and tellurium oxide (i.e., the glass powder must contain silicon oxide).
[0042] As one implementation method, the glass powder preparation steps include: Ingredients: Prepare glass raw materials, which include B2O3 (19% by mass), Al2O3 (7% by mass), PbO (53% by mass), Bi2O3 (16% by mass), SiO2 (2% by mass), and ZnO (3% by mass).
[0043] Melting: The uniformly mixed glass raw materials are poured into a platinum crucible and placed in a sintering furnace. Sintering begins after the preset temperature is reached, with the maximum sintering temperature set at 1200℃ and the holding time at 2.5 hours. Then, a two-roll cold rolling mill is used to cool and crush the molten glass into sheets.
[0044] Coarse grinding: Place glass fragments and zirconia balls into the jar of a planetary ball mill, add counterweights, and start grinding. Run for 12 minutes at a speed of 180 r / min. Then, sieve the ball-milled glass powder through a 200-mesh sieve to obtain coarse powder.
[0045] Fine grinding: Place the coarse powder, zirconia balls, and anhydrous ethanol into the jar of a planetary ball mill, add counterweights, and start grinding again. Run for 90 minutes at a speed of 450 r / min. Dry in a drying oven (85°C), and then sieve the dried glass powder through a 200-mesh sieve to obtain fine glass powder.
[0046] Testing: The D50 of the glass powder was measured using a laser particle size analyzer, and a particle size of 1.50-1.60 was considered suitable.
[0047] In one embodiment, in step S2 above, the mass of the glass powder accounts for 1%-30% of the total mass of the reaction system (i.e., the reaction system composed of the second solvent, the glass powder, and the first solution).
[0048] In one implementation, in step S2 above, the mass ratio of the first solution to the glass powder is (0.5~50):100, specifically 0.5:100, 1:100, 2:100, 5:100, 10:100, 20:100, 30:100, 40:100, 50:100, etc., or any combination of the above ratios.
[0049] In one embodiment, in step S2 above, the grafting density of the modified glass powder is (0.01~10)×10⁻¹⁰. -3 nm -2 (That is, the number of functionalized polymer chains grafted per square nanometer area on the surface of the glass powder is (0.01~10)×10) -3 The grafting density of the modified glass powder can specifically be 0.01 × 10⁻⁶. -3 nm -2 0.1×10 -3 nm -2 0.5×10 -3 nm -2 1×10 -3 nm -2 2×10 -3 nm -2 3×10 -3 nm -2 4×10 -3 nm -2 5×10 -3 nm -2 6×10 -3 nm -2 7×10 -3 nm -2 8×10 -3 nm -2 9×10 -3 nm -2 10×10 -3 nm -2"etc." can also be any combination of the above values.
[0050] In one embodiment, in step S2 above, the modified glass powder is further subjected to steps such as washing with anhydrous ethanol, drying, and sieving.
[0051] The following examples illustrate the preparation steps of modified glass powder: 1. Preparation of the first solution: Diethylene glycol dibutyl ether solvent, 1,3-butadiene (BR) and styrene (St) monomers (mass ratio 7:3), and N,N-dimethyltetrahydrofurfurylamine structure control agent were added to the reaction vessel. Stirring was started, and sec-butyllithium initiator was added. The reaction yielded the polymer chain SB-Li; the mass percentage of the monomers in the reaction solution was 15%. This step allows for the design of random or block molecular structures and different molecular weights of the polymer chain according to requirements. This example uses a random structure, with a designed molecular weight of 10,000. The reaction equation for this process is as follows (specifically, the reaction equation for the reaction of m styrene molecules with n butadiene molecules to generate the polymer chain SB-Li):
[0052] After reacting for a period of time (e.g., 1 hour), silicon tetrachloride (SiCl4) is added to the reaction solution to cap the polymer chain SB-Li. The molar ratio of silicon tetrachloride to SB-Li is 1.2:1. The mixture is stirred for a period of time (e.g., 1 hour) to prepare a first solution containing functionalized polymer chains SBR-SiCl3 that can react with glass powder. The reaction formula for this process is as follows (specifically, the reaction formula for capping the SB-Li polymer chain with silicon tetrachloride to generate the functionalized polymer chain SBR-SiCl3):
[0053] 2. Preparation of modified glass powder: Diethylene glycol dibutyl ether solvent, glass powder, a first solution containing functionalized polymer chains SBR-SiCl3, and zirconia balls were placed in a planetary ball mill jar. A nitrogen atmosphere was maintained inside the jar. After balancing, grinding was started and ran for 30 minutes at a speed of 500 rpm. The Si-Cl bonds at the ends of the functionalized polymer chains SBR-SiCl3 first undergo a hydrolysis reaction with the bound water on the surface of the glass powder (e.g., silica), removing HCl molecules and generating SBR-Si-(OH). X Then, it reacts with the Si-OH on the surface of the glass powder to form Si-O-Si bonds, thereby grafting SBR onto the surface of the glass powder. The modified glass powder is washed with anhydrous ethanol, dried, and sieved through a 200-mesh sieve to obtain functionalized polymer chain SBR-SiCl3 modified glass powder. The reaction formula for this process is as follows: SBR-SiCl3+Si-OH→SBR-SiCl2-O-Si+HCl In the above reaction, the grafting density of the modified glass powder can be adjusted by changing the mass ratio of the first solution to the glass powder.
[0054] This invention also provides a modified glass powder for use in photovoltaic silver paste, which is prepared using the modified glass powder preparation method described above.
[0055] This invention also provides a photovoltaic silver paste, which, by mass percentage, comprises: 85%-92% silver powder, 1%-4% modified glass powder, 0.1%-1% dispersant, 0.4%-1% silicone oil, 0.1%-2% thixotropic agent, 1%-4% organic resin, and 4%-10% organic solvent. The modified glass powder is the modified glass powder described above, or the modified glass powder is prepared using the modified glass powder preparation method described above.
[0056] In one embodiment, the silver powder is one or more of micron-sized silver powder and nano-sized silver powder. The mass percentage of the silver powder can be 85%, 86%, 87%, 88%, 89%, 90%, 91%, 92%, etc., or any combination of the above values.
[0057] In one embodiment, the mass percentage of the modified glass powder can be 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, etc., or any combination of the above values.
[0058] In one embodiment, the dispersant includes one or more of amines, amides, fatty acids, phosphate esters, polyoxyethylene ethers, and polymeric dispersants. The mass percentage of the dispersant can be 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, etc., or any combination of the above values.
[0059] In one embodiment, the silicone oil can be one or more of the grades 5, 10, 20, 50, 100, and 200. The mass percentage of the silicone oil can be 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, etc., or any combination of the above values.
[0060] In one embodiment, the thixotropic agent includes one or more of hydrogenated castor oil and polyamide wax. The mass percentage of the thixotropic agent can be 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9%, 1%, 1.2%, 1.5%, 2%, etc., or any combination of the above values.
[0061] In one embodiment, the organic resin includes one or more of hydrogenated styrene-isoprene copolymer, hydrogenated styrene-butadiene copolymer, cellulose, polyvinyl butyral, polyacrylic acid, and cellulose acetate butyrate. The mass percentage of the organic resin can be 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, etc., or any combination of the above values.
[0062] In one embodiment, the organic solvent includes one or more of diethylene glycol butyl ether acetate, dodecyl alcohol ester, hexadecyl alcohol ester, diethylene glycol dibutyl ether, phthalate, and benzyl benzoate. The mass percentage of the organic solvent can be 4%, 4.5%, 5%, 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, 9.5%, 10%, etc., or any combination of the above values.
[0063] This invention also provides a solar cell, including electrodes, which are obtained by sintering photovoltaic silver paste as described above. Specifically, the solar cell can be a TOPCon (Tunnel Oxide Passivated Contact) solar cell. Specifically, the photovoltaic silver paste is screen-printed, dried, and sintered onto the surface of the silicon wafer to form metal grid lines, thus forming the desired electrodes. For other technical features of this electrode, please refer to the prior art, which will not be repeated here.
[0064] To verify the technical effect of the modified glass powder in this application, the following comparative experiment was designed. The main procedure of the comparative experiment is as follows: First, unmodified glass powder, KH-570 silane coupling agent modified glass powder, and functionalized polymer chain SBR-SiCl3 modified glass powder were prepared respectively, and the fineness, sedimentation characteristics, and SEM of the three glass powders were tested. Then, photovoltaic silver paste was prepared using the three glass powders respectively, and the printability, thixotropy, viscosity change, and electrical properties were tested.
[0065] I. Preparation of Three Types of Glass Powders (1) Preparation of glass powder, the preparation steps include: Ingredients: Prepare glass raw materials, which include B2O3 (19% by mass), Al2O3 (7% by mass), PbO (53% by mass), Bi2O3 (16% by mass), SiO2 (2% by mass), and ZnO (3% by mass).
[0066] Melting: The uniformly mixed glass raw materials are poured into a platinum crucible and placed in a sintering furnace. Sintering begins after the preset temperature is reached, with the maximum sintering temperature set at 1200℃ and the holding time at 2.5 hours. Then, a two-roll cold rolling mill is used to cool and crush the molten glass into sheets.
[0067] Coarse grinding: Place glass fragments and zirconia balls into the jar of a planetary ball mill, add counterweights, and start grinding. Run for 12 minutes at a speed of 180 r / min. Then, sieve the ball-milled glass powder through a 200-mesh sieve to obtain coarse powder.
[0068] Fine grinding: Place the coarse powder, zirconia balls, and anhydrous ethanol into the jar of a planetary ball mill, add counterweights, and start grinding again. Run for 90 minutes at a speed of 450 r / min. Dry in a drying oven (85°C), and then sieve the dried glass powder through a 200-mesh sieve to obtain fine glass powder.
[0069] Testing: The D50 of the glass powder was measured using a laser particle size analyzer, and a particle size of 1.50-1.60 was considered suitable.
[0070] (2) Preparation of functionalized polymer chain SBR-SiCl3 solution, the preparation steps include: Add diethylene glycol dibutyl ether solvent (manufacturer: Shanghai Aladdin Biochemical Technology Co., Ltd., product model: D104427), 1,3-butadiene (BR) (manufacturer: China Petroleum & Chemical Corporation, polymerization grade), and styrene (St) (manufacturer: Shanghai Aladdin Biochemical Technology Co., Ltd., product model: S110376) (mass ratio 7:3) and N,N-dimethyltetrahydrofurfurylamine structure control agent (manufacturer: Henan Alpha Chemical Co., Ltd., purity 98%) to a 250ml three-necked flask. Start stirring and add sec-butyllithium initiator (manufacturer: Shanghai Maclean Biochemical Technology Co., Ltd., product model: B802688). The reaction yields the polymer chain SB-Li; the mass percentage of the monomers in the reaction solution is 15%. After reacting for 1 hour, silicon tetrachloride (SiCl4) (manufacturer: Huawi Ruike Co., Ltd., analytical grade) was added to the reaction solution to end the polymer chain SB-Li. The molar mass ratio of silicon tetrachloride to polymer chain SB-Li was 1.2:1. After stirring for 1 hour, a functionalized polymer chain SBR-SiCl3 solution was prepared.
[0071] (3) Preparation of functionalized polymer chain SBR-SiCl3 modified glass powder, the preparation steps include: Diethylene glycol dibutyl ether solvent, the aforementioned glass powder, the aforementioned functionalized polymer chain SBR-SiCl3 solution, and zirconia balls were placed into a planetary ball mill jar. A nitrogen atmosphere was maintained inside the jar. After balancing, grinding was started and ran for 30 minutes at a speed of 500 r / min. The Si-Cl bonds at the ends of the functionalized polymer chain SBR-SiCl3 first undergo a hydrolysis reaction with the bound water on the surface of the glass powder, removing HCl molecules and generating SBR-Si-(OH). X Then, it reacts with the Si-OH on the surface of the glass powder to form Si-O-Si bonds, thereby grafting SBR onto the surface of the glass powder. The modified glass powder is washed with anhydrous ethanol, dried, and sieved through a 200-mesh sieve to obtain functionalized polymer chain SBR-SiCl3 modified glass powder.
[0072] During the reaction, by adjusting the mass ratio of the functionalized polymer chain SBR-SiCl3 solution to glass powder to 3.5:100, 15:100, and 30:100, three different grafting densities of functionalized polymer chain SBR-SiCl3 modified glass powder were prepared, corresponding to grafting densities of 0.5 × 10⁻⁶ and 0.5 × 10⁻⁶, respectively. -3 nm -2 2.5×10 -3 nm -2 5×10 -3 nm -2 .
[0073] (4) Preparation of KH-570 silane coupling agent modified glass powder, the preparation steps include: Diethylene glycol dibutyl ether solvent, the aforementioned glass powder, KH-570 silane coupling agent, and zirconia balls were placed in the jar of a planetary ball mill. A nitrogen atmosphere was maintained inside the jar. After balancing, grinding was started and ran for 30 minutes at a speed of 500 r / min. The mixture was then washed with anhydrous ethanol, dried, and sieved through a 200-mesh sieve to obtain a grafting density of 2.5 × 10⁻⁶. -3 nm -2 KH-570 silane coupling agent modified glass powder.
[0074] (5) Take a portion of the unmodified glass powder as unmodified glass powder.
[0075] II. Preparation of Photovoltaic Silver Paste [Example 1] The photovoltaic silver paste in Example 1 comprises: a grafting density of 0.5 × 10⁻⁶. -3 nm -2The photovoltaic silver paste is prepared by mixing 2% functionalized SBR-SiCl3 modified glass powder, 88% silver powder, and 10% carrier (containing 0.1% fatty acid dispersant, 0.1% polyamide wax, 0.6% grade 200 silicone oil, 1.0% hydrogenated styrene-isoprene copolymer, 5.2% diethylene glycol butyl acetate, and 3% phthalate). The raw materials are then uniformly dispersed in a double planetary homogenizer, and the mixture is further ground uniformly in a three-roll mill to ensure a fineness within 5 μm, yielding the photovoltaic silver paste. The viscosity of the photovoltaic silver paste at 50 rpm is 50-90 Pa·s.
[0076] [Example 2] The photovoltaic silver paste in Example 2 comprises: a grafting density of 2.5 × 10⁻⁶. -3 nm -2 The photovoltaic silver paste is prepared by mixing 2% functionalized SBR-SiCl3 modified glass powder, 88% silver powder, and 10% carrier (containing 0.1% fatty acid dispersant, 0.1% polyamide wax, 0.6% grade 200 silicone oil, 1.0% hydrogenated styrene-isoprene copolymer, 5.2% diethylene glycol butyl acetate, and 3% phthalate). The raw materials are then uniformly dispersed in a double planetary homogenizer, and the mixture is further ground uniformly in a three-roll mill to ensure a fineness within 5 μm, yielding the photovoltaic silver paste. The viscosity of the photovoltaic silver paste at 50 rpm is 50-90 Pa·s.
[0077] [Example 3] The photovoltaic silver paste in Example 3 includes: a grafting density of 5×10 -3 nm -2 The photovoltaic silver paste is prepared by mixing 2% functionalized SBR-SiCl3 modified glass powder, 88% silver powder, and 10% carrier (containing 0.1% fatty acid dispersant, 0.1% polyamide wax, 0.6% grade 200 silicone oil, 1.0% hydrogenated styrene-isoprene copolymer, 5.2% diethylene glycol butyl acetate, and 3% phthalate). The raw materials are then uniformly dispersed in a double planetary homogenizer, and the mixture is further ground uniformly in a three-roll mill to ensure a fineness within 5 μm, yielding the photovoltaic silver paste. The viscosity of the photovoltaic silver paste at 50 rpm is 50-90 Pa·s.
[0078] [Comparative Example 1] The photovoltaic silver paste in Comparative Example 1 comprises: 2% unmodified glass powder, 88% silver powder, and 10% carrier (0.1% fatty acid dispersant, 0.1% polyamide wax, 0.6% grade 200 silicone oil, 1.0% hydrogenated styrene-isoprene copolymer, 5.2% diethylene glycol butyl acetate, and 3% phthalate). The above raw materials are mixed and dispersed evenly in a double planetary homogenizer, and then the mixture is ground evenly in a three-roll mill to ensure a fineness within 5 μm, thus obtaining the photovoltaic silver paste. The viscosity of the photovoltaic silver paste at 50 rpm is 50-90 Pa·s.
[0079] [Comparative Example 2] The photovoltaic silver paste in Comparative Example 2 comprises: 2% KH-570 silane coupling agent modified glass powder, 88% silver powder, and 10% carrier (0.1% fatty acid dispersant, 0.1% polyamide wax, 0.6% grade 200 silicone oil, 1.0% hydrogenated styrene-isoprene copolymer, 5.2% diethylene glycol butyl acetate, and 3% phthalate). The above raw materials are mixed and dispersed evenly in a double planetary homogenizer, and then the mixture is ground evenly in a three-roll mill to ensure a fineness within 5 μm, thus obtaining the photovoltaic silver paste. The 50 rpm viscosity of the photovoltaic silver paste is 50-90 Pa·s.
[0080] III. Performance Testing The glass powder and photovoltaic silver paste in Examples 1-3 and Comparative Examples 1-2 were subjected to relevant performance tests, and the test process is as follows: (1) The particle size of each glass powder was tested by a laser particle size analyzer, and the fineness of the glass slurry prepared by each glass powder was tested by a fineness analyzer. The results are shown in Table 1.
[0081] Table 1 Glass Particle Size and Fineness
[0082] As shown in the table above, the D50 of the functionalized polymer chain SBR-SiCl3 modified glass powder decreased after modification. This indicates that the polymer chains form physical isolation on the glass surface, reducing surface energy and effectively weakening powder agglomeration. Simultaneously, the Gn number (D90 / D10) increased, indicating a more concentrated glass particle size distribution, more controllable glass flow during subsequent sintering, more uniform corrosion of the silicon wafer antireflective layer, and improved ohmic contact. Furthermore, the finer particle size of the glass slurry prepared from the polymer chain-modified glass further demonstrates that the polymer chains can prevent glass agglomeration.
[0083] (2) Unmodified glass powder, KH-570 silane coupling agent modified glass powder, and functionalized polymer chain SBR-SiCl3 modified glass powder (grafting density of 2.5×10⁻⁶) were used. -3 nm -2 Dissolve each ingredient separately in diethylene glycol butyl ether acetate, mix thoroughly, and let stand for 10 minutes. Figures 1 to 3 As can be seen, unmodified glass powder exhibits significant phase separation, followed by KH-570 silane coupling agent-modified glass powder, while functionalized polymer chain SBR-SiCl3-modified glass powder shows no phase separation from the solvent. This is because the polymer chains grafted onto the glass surface are non-polar substances, weakening the polarity of the glass and thus increasing the compatibility between the glass and the organic carrier.
[0084] (3) Unmodified glass powder, KH-570 silane coupling agent modified glass powder, and functionalized polymer chain SBR-SiCl3 modified glass powder (grafting density of 2.5×10⁻⁶) were respectively tested. -3 nm -2 Perform SEM scanning. From Figures 4 to 6 As can be seen, unmodified glass powder exhibits significant agglomeration, even large clumps. The agglomeration of glass powder modified with KH-570 silane coupling agent is slightly improved, but localized agglomeration still exists. This is because KH-570 coupling agent is a small molecule with a molecular weight of only a few hundred, resulting in a very weak physical isolating effect on the glass surface. In contrast, the agglomeration of functionalized polymer chain SBR-SiCl3 modified glass powder is significantly improved, resulting in uniform dispersion.
[0085] (4) The thixotropy of the photovoltaic silver pastes in Example 2, Comparative Example 1, and Comparative Example 2 was tested using an Anton Paar rheometer. The photovoltaic silver pastes went through three stages: low shear, high shear, and low shear. The viscosity difference between the two low shear stages was compared. The smaller the difference, the better the elastic recovery ability of the silver paste. According to the test results, Example 2 had the best shear thinning ability and elastic recovery state. This is because the polymer chain modified glass used in Example 2 has a very long polymer chain, which is sufficient to entangle with the resin chain in the organic carrier, so that the glass is uniformly dispersed in the silver paste.
[0086] (5) The viscosity change of the photovoltaic silver paste in Examples 1-3 and Comparative Examples 1-2 was tested at 50 revolutions over 15 days. The results are shown in Table 2 (the viscosity unit in Table 2 is Pa·s).
[0087] Table 2. Viscosity change of silver paste at 50 revolutions over 15 days
[0088] As can be seen from the table above, the silver pastes prepared using polymer chain-modified glass in Examples 1-3 had lower viscosities than those in Comparative Examples 1 and 2, indicating that the compatibility between the modified glass and the organic carrier was improved, resulting in better dispersibility in the silver paste. Furthermore, the silver pastes from Examples 1-3 exhibited good viscosity stability over 15 days, with virtually no viscosity fluctuations, which is beneficial for long-term storage.
[0089] (6) Printability Test: The photovoltaic silver pastes from Examples 1-3 and Comparative Examples 1-2 were printed onto silicon wafers using screen printing technology to form wet film grid lines. The wet film grid lines were then sintered, causing the organic carrier to volatilize and the glass and silver powder to fuse together. Simultaneously, the flowing glass etched the passivation layer of the silicon wafer, forming conductive contact points to obtain the solar cell. The silver paste printing used a Maiwei machine with a printing speed of 550-1000 mm / s; screen parameters were 224 grids, 700 mesh, 5 wire diameter, 10 yarn thickness, 3 film thickness, and 5.5 μm opening; the silicon wafer size was 210 mm × 183 mm; and the wet weight was controlled at 28-30 mg. Sintering temperature and belt speed: 760℃, 19 m / min.
[0090] The broken grid lines of each solar cell were detected using an EL testing machine. The non-luminescent area on the cell indicates a broken electrode grid line, which appears as a black line. Figures 7 to 11 As can be seen, Comparative Example 1 and Comparative Example 2 show severe grid breakage (e.g. Figure 7 and Figure 8 (The location indicated by the middle arrow is the location of the broken grid). Examples 1, 2, and 3 have no broken grids, indicating that the photovoltaic silver paste of Examples 1, 2, and 3 has good printing performance.
[0091] Electrical performance testing: The solar cells were processed using a light-injection annealing furnace and a laser device to optimize the conductive contact of the cell grid lines. The light-injection annealing furnace was model DM-032F, with a maximum temperature of 220℃; the laser parameters were 44KV and 19W.
[0092] The electrical performance of each solar cell was tested using a Maiwei IV-EL tester, and the results are shown in Table 3. In the table, Voc is the open-circuit voltage of the solar cell, Isc is the short-circuit current, Rs is the series resistance, Rsh is the parallel resistance, FF is the fill factor, and Eff is the electrical efficiency.
[0093] Table 3 Electrical performance test data
[0094] As can be seen from the table above, compared with Comparative Examples 1 and 2, the electrical performance efficiency (Eff) of Examples 1, 2, and 3 is significantly improved. This indicates that the glass dispersion in Comparative Examples 1 and 2 is uneven, and the glass phase agglomerates locally during the sintering stage, leading to excessive corrosion of the silicon wafer in that area (damaging the PN junction), while other areas lacking glass have poor contact, resulting in leakage current, low parallel resistance, and efficiency loss in the solar cell. At the same time, agglomeration leads to uneven conductive channels, increased and unstable series resistance, and poor overall electrical performance.
[0095] In summary, the method described in this application effectively solves the problems of large particle size, easy sedimentation, and severe agglomeration in traditional unmodified glass or silane coupling agent modified glass. Correspondingly, the silver paste prepared in this application exhibits significantly improved printability, better thixotropic properties, stable viscosity, and enhanced electrical properties.
[0096] The above are merely specific embodiments of the present invention, but the scope of protection of the present invention is not limited thereto. Any variations or substitutions that can be easily conceived by those skilled in the art within the technical scope disclosed in the present invention should be included within the scope of protection of the present invention. Therefore, the scope of protection of the present invention should be determined by the scope of the claims.
Claims
1. A method for preparing modified glass powder, characterized in that, Includes the following steps: S1: A first solvent, a polymerizing monomer, a structure control agent, and an initiator are mixed and reacted to obtain a polymer chain; then silicon tetrachloride is added to the reaction solution to end-cap the polymer chain, resulting in a first solution containing a functionalized polymer chain; wherein the polymerizing monomer includes one or more of styrene monomers, conjugated diene monomers, and vinyl monomers. S2: The second solvent, silica-containing glass powder, and the first solution are mixed to graft the functionalized polymer onto the surface of the glass powder, thereby obtaining modified glass powder; wherein the mass ratio of the first solution to the glass powder is (0.5~50):100, and the grafting density of the modified glass powder is (0.01~10)×10⁻⁶. -3 nm -2 .
2. The method for preparing modified glass powder as described in claim 1, characterized in that, The styrene monomers include one or more of styrene, α-methylstyrene, and p-methylstyrene; the conjugated diene monomers include one or more of 1,3-butadiene and isoprene; and the vinyl monomers include one or more of acrylates, acrylonitrile, and methyl vinyl ketone.
3. The method for preparing modified glass powder as described in claim 1, characterized in that, The structure control agent includes one or more of ether structure control agents, amine structure control agents, and alkali metal salts; the ether structure control agent includes one or more of tetrahydrofuran, diethylene glycol dibutyl ether, and crown ethers; the amine structure control agent includes one or more of N,N-dimethyltetrahydrofurfurylamine, N,N,N,N-tetramethyltetrahydrofurfurylamine, triethylamine, and tetrahydropyrrole; and the alkali metal salt includes potassium tert-butoxy.
4. The method for preparing modified glass powder as described in claim 1, characterized in that, The initiator includes one or more of alkyllithium, alkali metal, nucleophile, and alkylaluminum-alkali metal complex; the alkyllithium includes one or more of n-butyllithium, sec-butyllithium, tert-butyllithium, and multifunctional lithium; the alkali metal includes one or more of lithium, sodium, and potassium; and the nucleophile includes one or more of sodium hydroxide, sodium alkoxide, and amine nucleophiles.
5. The method for preparing modified glass powder as described in claim 1, characterized in that, The first solvent includes one or more of n-hexane, cyclohexane, benzene, toluene, tetrahydrofuran, diethyl ether, 1,4-dioxane, and diethylene glycol dibutyl ether; and / or the second solvent includes one or more of n-hexane, cyclohexane, benzene, toluene, tetrahydrofuran, diethyl ether, 1,4-dioxane, and diethylene glycol dibutyl ether.
6. The method for preparing modified glass powder as described in claim 1, characterized in that, The glass powder is silicon oxide; or, the glass powder includes silicon oxide and one or more of boron oxide, bismuth oxide, zinc oxide, lithium oxide, calcium oxide, tungsten oxide, copper oxide, iron oxide, and tellurium oxide.
7. The method for preparing modified glass powder according to any one of claims 1-6, characterized in that, In step S2 above, the mass of the glass powder accounts for 1%-30% of the total mass of the reaction system composed of the second solvent, the glass powder, and the first solution.
8. A modified glass powder, characterized in that, It is prepared by the method of any one of claims 1-7.
9. A photovoltaic silver paste, characterized in that, The photovoltaic silver paste comprises, by weight percentage: 85%-92% silver powder, 1%-4% modified glass powder, 0.1%-1% dispersant, 0.4%-1% silicone oil, 0.1%-2% thixotropic agent, 1%-4% organic resin, and 4%-10% organic solvent; the modified glass powder is the modified glass powder as described in claim 8 or prepared by the method of preparing modified glass powder as described in any one of claims 1-7.
10. A solar cell, characterized in that, Includes electrodes, which are obtained by sintering photovoltaic silver paste as described in claim 9.
Citation Information
Patent Citations
Method for preparing terminal group functional solution polymerized butadiene styrene rubber filling white carbon black composite material
CN101319064A
Modified glass powder for PERC back silver paste as well as preparation method and application of modified glass powder
CN113880435A
Front silver paste for solar cell with low contact resistance and high photoelectric conversion efficiency and preparation method of front silver paste
CN114664475A